1998
DOI: 10.4269/ajtmh.1998.58.240
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular hemodynamics and in vivo evidence for the role of intercellular adhesion molecule-1 in the sequestration of infected red blood cells in a mouse model of lethal malaria.

Abstract: The cytoadherence of infected red blood cells (IRBCs) to the vascular endothelium is the major cause of IRBC sequestration and vessel blockage in the cerebral form of human malaria. Among the rodent models of malaria, Plasmodium yoelii 17XL-infected mice show many similarities with the human cerebral malaria caused by P. falciparum. In both, the sequestration of IRBCs in the brain vessels is secondary to the cytoadherence of IRBCs to the vascular endothelium. Similar to P. falciparum infection in the human but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 52 publications
(61 reference statements)
4
22
0
Order By: Relevance
“…Our data do not support the assertion that elevated vcam-1 corresponds to ECM, as we observed slightly higher vcam-1 mRNA levels in ⌬hmgb2 ANKA-infected mice at d6 postinfection than in WT P. berghei ANKA-infected C57BL/6 mice, suggesting an uncertain or perhaps protective role for this adhesion molecule in our model. In concordance with our observation of a predominant role for ICAM-1 compared to VCAM-1 in malaria pathogenesis, infusion of an anti-ICAM-1 but not an anti-VCAM-1 monoclonal antibody prevented cytoadherence of infected erythrocytes in a P. yoelii model of ECM (65), in addition to in vivo evidence for the role of ICAM-1 in the sequestration of infected red blood cells in a mouse model of lethal malaria (66). In contrast, the transcript level of the cytoprotective heme oxygenase gene (hmox-1) was markedly increased at d6 in ⌬hmgb2 ANKAinfected C57BL/6 mice and was thus consistent with the literature (9-11).…”
Section: Discussionsupporting
confidence: 67%
“…Our data do not support the assertion that elevated vcam-1 corresponds to ECM, as we observed slightly higher vcam-1 mRNA levels in ⌬hmgb2 ANKA-infected mice at d6 postinfection than in WT P. berghei ANKA-infected C57BL/6 mice, suggesting an uncertain or perhaps protective role for this adhesion molecule in our model. In concordance with our observation of a predominant role for ICAM-1 compared to VCAM-1 in malaria pathogenesis, infusion of an anti-ICAM-1 but not an anti-VCAM-1 monoclonal antibody prevented cytoadherence of infected erythrocytes in a P. yoelii model of ECM (65), in addition to in vivo evidence for the role of ICAM-1 in the sequestration of infected red blood cells in a mouse model of lethal malaria (66). In contrast, the transcript level of the cytoprotective heme oxygenase gene (hmox-1) was markedly increased at d6 in ⌬hmgb2 ANKAinfected C57BL/6 mice and was thus consistent with the literature (9-11).…”
Section: Discussionsupporting
confidence: 67%
“…Upregulation of mediators of pathology during CM has been reported previously in both murine (19) and human (33) malaria. Hence, it was important to document these phenomena in this model.…”
Section: Resultsmentioning
confidence: 96%
“…19 Importantly, in our recent studies, we have found that anti-ICAM MAb can reverse cytoadherence in vivo and release schizonts into the circulation. 20 Thus, ICAM-1, and not VCAM-1, is a likely cytoadherence molecule in this model.…”
Section: Discussionmentioning
confidence: 99%